The Relational Dynamics of Becoming Popular Feminist Subjects: The World March of Women and Rural/Peasant Women’s Organizing in Brazil in the 2000s - Masson, Dominique; Bastien, Elsa Beaulieu (Latin American perspectives, 2021)
The constitution and consolidation of rural and peasant women as popular feminist subjects in Brazil are the result not only of processes internal to these constituencies but also of relational dynamics involving cross-class and cross-movement popular activist organizations. Since the end of the 1990s, organizations and activists identifying with the World March of Women in western Rio Grande do Norte and at the national scale have consciously engaged with rural and peasant women and assisted them in becoming and consolidating themselves as popular feminist subjects. Relational dynamics have also been important in the (unfinished) process of transforming, extending, and deepening the dual meaning of “popular feminism” in Brazil. A constituição e consolidação das mulheres rurais e camponesas como sujeitos feministas populares no Brasil são o resultado não apenas de processos internos desses grupos, mas também das dinâmicas relacionais que envolvem organizações ativistas populares de classes e movimentos. Desde o final da década de 1990, organizações e ativistas que se identificam com a Marcha Mundial das Mulheres da região Oeste do Rio Grande do Norte e em escala nacional têm se engajado conscientemente com as mulheres rurais e camponesas, ajudando as mesmas a se tornarem e consolidarem como sujeitos feministas populares. As dinâmicas relacionais têm sido importantes também no processo (incompleto) de transformação, extensão e aprofundamento do duplo significado de “feminismo popular” no Brasil.